An Ecological Momentary Intervention for weight loss and healthy eating via smartphone and Internet: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Boh, Bastiaan; Lemmens, Lotte; Jansen, Anita; Nederkoorn, Chantal; Kerkhofs, Vincent; Spanakis, Gerasimos; Weiss, Gerhard; Roefs, Anne
Abstract Background Long-term weight loss maintenance is difficult to achieve. Effectiveness of obesity interventions could be increased by providing extended treatment, and by focusing on person-environment interactions. Ecological Momentary Intervention (EMI) can account for these two factors by allowing an indefinite extension of a treatment protocol in everyday life. EMI relies on observations in daily life to intervene by providing appropriate in-the-moment treatment. The Think Slim intervention is an EMI based on the principles of cognitive behavioural therapy (CBT), and its effectiveness will be investigated in the current study. Methods A randomised controlled trial (RCT) will be conducted. At least 134 overweight adults (body mass index (BMI) above 25 kg/m2 ) will be randomly assigned to an 8-week immediate intervention group (Diet + Think Slim intervention, n  = 67) or to an 8-week diet-only control group (followed by the Think Slim intervention, n  = 67). The Think Slim intervention consists of (1) an app-based EMI that estimates and intervenes when people are likely to overeat, based on Ecological Momentary Assessment data, and (2) ten online computerised CBT sessions which work in conjunction with an EMI module in the app. The primary outcome is BMI. Secondary outcomes include (1) scores on self-report questionnaires for dysfunctional thinking, eating styles, eating disorder pathology, general psychological symptomatology, and self-esteem, and (2) eating patterns, investigated via network analysis. Primary and secondary outcomes will be obtained at pre- and post-intervention measurements, and at 3- and 12-month follow-up measurements. Discussion This is the first EMI aimed at treating obesity via a cognitive approach, provided via a smartphone app and the Internet, in the context of an RCT. Trial registration This trial has been registered at the Netherlands Trial Register, part of the Dutch Cochrane Centre (NTR5473 ; registration date: 26 October 2015).